INOVASI E-COMMERCE B2B: APLIKASI PEMESANAN ONLINE BERBASIS WEB DI PT SADANG JAYA - Clive Riady; Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
PT Sadang Jaya is a snack food production company that has a good reputation in the market, but along with the growth of the company and the increase in the number of distributors, order management which is still done manually via WhatsApp or telephone is becoming increasingly inefficient and prone to errors. This results in irregular order queues and discrepancies with the order that should be, as well as increasing the risk of recording errors that can cause delays in order fulfillment and customer dissatisfaction. To overcome these challenges, it is necessary to implement a B2B (Business-to-Business) eCommerce system that allows business transactions to be more efficient. This research aims to design and develop a web-based online ordering application that not only increases transparency in stock management and reduces recording errors, but also accelerates the order fulfillment process and strengthens business relationships with distributors. By using Angular as a frontend framework and PostgreSQL as a database managed through pgAdmin, as well as applying Agile methodology that allows rapid iteration and adaptation, this application is expected to meet the business needs of PT Sadang Jaya effectively, while utilizing the great potential of B2B eCommerce to expand market reach and increase distributor satisfaction through more integrated services.